An Inflammatory Composite Score Predicts Mycobacterial Immune Reconstitution Inflammatory Syndrome in People with Advanced HIV: A Prospective International Cohort Study. (6th August 2020) - Vinhaes, Caian L; Sheikh, Virginia; Oliveira-de-Souza, Deivide; Wang, Jing; Rupert, Adam; Roby, Gregg; Arriaga, María B; Fukutani, Kiyoshi F; Sawe, Fred; Shaffer, Doug; Ananworanich, Jintanat; Phanuphak, Nittaya; et al.
Abstract: Background: Immune reconstitution inflammatory syndrome (IRIS) is a common cause of morbidity among people with human immunodeficiency virus (PWH) who initiate antiretroviral therapy (ART) with severe lymphopenia. Easily accessible tools that reliably predict emergence and elucidate pathogenesis of IRIS are needed to facilitate improved clinical management. Methods: Plasma levels of biomarkers were measured before ART initiation in a large multinational cohort of ART-naive PWH with severe immunosuppression (CD4 + count <100 cells/mm 3 ) in United States, Kenya, and Thailand. We performed a series of multiparametric analyses of inflammatory and clinical biomarkers and developed a composite score merging relevant biomarkers for use in a prediction model. Results: We identified a distinct baseline inflammatory profile and changes in inflammatory networks among biomarkers in participants who subsequently developed mycobacterial or viral IRIS. We also developed a composite score incorporating biomarkers associated with IRIS (interleukin-6 [IL-6], IL-10, IL-27, sCD14, interferon-γ, tumor necrosis factor-α, hyaluronic acid, D-dimer, body mass index, and hemoglobin) that accurately predicted mycobacterial IRIS and death in this cohort. Conclusions: Systemic inflammatory profiles in PWH with severe immunosuppression are predictive of IRIS. Composite scores for the prediction of mycobacterial IRIS and death could be useful for risk stratification in PWH and lymphopenia initiating ART. Clinical Trials Registration: NCT00286767. Abstract : A composite score using clinical and inflammatory measurements assessed in people with HIV and severe lymphopenia prior to antiretroviral therapy was designed to predict immune reconstitution inflammatory syndrome associated with mycobacterial or viral infections in a prospective international study.